DEVELOPMENT OF MANAGENMENT STRATEGY THROUGH ANALYSIS OF ADOPTION INTENTION AND INFLUENCE FACTORS OF AUTONOMOUS VEHICLES CENTERING ON VALUE-BASED ADOPTION MODELS - Yu, Minsang (Global journal of Business and Integral Security, 2022)
This study was conducted to derive business strategies to help commercialize and popularize autonomous vehicles by exploring and demonstrating factors that affect the value and acceptance of autonomous vehicles perceived by potential buyers and future users of autonomous vehicles, one of the state-of-the-art new technologies of the Fourth Industrial Revolution. Under the consciousness and goals of these problems, this study verified the effects of ’perceived benefits’, ’perceived sacrifice’, ’perceived bias,’ and ’the perceived threat’ on ’perceived value’ and ’adoption intent’ through a survey and statistical analysis of general users, referring to the ’value-based adoption model’, a representative analytic theory of users’ perceived value for new technology, intent of acceptance, and intent for continued use. To this end, the study conducted a survey of 602 users interested in autonomous vehicles, and the collected survey data was conducted using the SPSS States 21.0 package program to analyze the frequency of demographic characteristics, analysis of technical statistics of sub-factors and detailed metrics that make up independent and dependent variables, analysis of validity and reliability, and simple and multiple iv regression between independent and dependent variables. The results of the analysis and verification of this study are summarized as follows. By demonstrating in various ways that individual users’ perceived benefits and optimistic prejudices against autonomous vehicles have a positive impact on perceived value and adoption intention, while perceived sacrifices and perceived threats have negative effects, this study derived and suggested a user-centered business strategy that can be applied and applied as necessary for the commercialization and popularization of autonomous vehicles. It is hoped that the results and conclusions of this study will be used as valid theoretical and practical guidelines and basic references to help the mid- to long-term development of autonomous vehicles.